Three-phase sample pollution inspection method based on aerogel three-dimensional SERS (Surface Enhanced Raman Scattering)
By using silver-loaded highly hydrophilic starch aerogels (ACA) combined with its collapse properties, the problem of internal aggregation of analytes in existing aerogels during detection is solved, enabling rapid detection of gas, liquid and solid phase samples. , accurate SERS quantitative analysis, significantly improving detection sensitivity and applicability.
Patent Information
- Application Number
- CN202411271977.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-11
AI Technical Summary
After the existing aerogels are loaded with analytes, the analytes are aggregated inside them, making it difficult to effectively detect large internal concentration areas in SERS detection, and the detection methods are not applicable to harmful substances that are difficult to dissolve in water, limiting the actual sample. Test.
Using cassava starch as the supporting structure, the silver-loaded highly hydrophilic starch aerogel (ACA) was synthesized through the reducing agent dialdehyde starch. The high specific surface area and porous structure of ACA, combined with its collapse properties, were used to achieve gas phase, liquid phase and Fast and accurate SERS quantitative analysis of solid three-phase samples.
Through ACA's high-ratio area and high adsorption, the 4-ATP of the gesture was successfully detected, and the trace detection of solid and liquid TBZ was achieved on the surface of Apple and Apple, which significantly improved the detection sensitivity and applicability.
Smart Images

Figure CN119334925A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sensing detection technology, and in particular to a three-phase sample contamination inspection method based on aerogel three-dimensional SERS. Background Art
[0002] Surface enhanced Raman spectroscopy (SERS) is a fast-response, non-destructive, real-time and ultra-sensitive detection technology that can also reflect the chemical fingerprint information of the analyte. At present, there are two main explanations for the SERS enhancement principle, electromagnetic enhancement (EM) and chemical enhancement (CM). Among them, the EM mode enhances the signal based on distance rather than chemical characteristics, provides the same SERS effect for various target molecules, and only produces a dramatic SERS enhancement when it is less than 5nm from the surface of the noble metal nanoparticles. Therefore, researchers call the location of the high-intensity electric field between the noble metal nanoparticles "hotspots". When the probe molecule is in the "hotspot", its SERS signal will be dramatically enhanced. It is common to achieve three-dimensional structures that adsorb more molecules of the analyte to increase the distribution density of the SERS "hotspots" by increasing the specific surface area. In the past few decades, various SERS substrates have been developed, including one-dimensional (1D) nanowires, two-dimensional (2D) planar arrays, and three-dimensional (3D) porous networks. The maximum number of SERS "hot spots" in 1D and 2D substrates is limited to a single Cartesian plane, however, for 3D SERS substrates, the spatial expansion along the z-axis dimension leads to a larger total surface area for 3D substrates. Due to the increase in specific surface area (SSA), more "hot spots" can be obtained from low-dimensional SERS to high-dimensional SERS, thereby obtaining higher detection sensitivity. In addition, compared with 1D and 2D substrates, 3D substrates show better light source utilization efficiency because they do not require precise laser focusing and can make full use of scattered light.
[0003] Aerogels are ideal plasmonic metal nanoparticle loading skeletons for SERS substrates due to their low density, controllable macroscopic shape, and diverse pore structures. Importantly, on the one hand, the 3D structure of aerogels can increase the number of "hot spots" along the x, y, and z axes. On the other hand, the ultra-high specific surface area and internal 3D network structure of aerogels can facilitate the capture of target molecules.
[0004] However, after the introduction of analytes into aerogels, they usually gather inside the aerogels. Since SERS is a surface sensing technology, most SERS measurements performed on aerogels as SERS substrates are targeted at the surface of the aerogels, and it is difficult to detect SERS performance in places where the actual analyte concentration is high. The utilization rate of aerogel "hot spots" is also limited to the surface of the aerogels, and the "hot spots" have not been truly increased. If the aerogels continue to achieve an increase in the concentration of "hot spots" and analytes after loading the analytes, such as the collapse of the aerogels, the number of "hot spots" on the aerogel surface will increase, resulting in stronger SERS performance, and the sensitivity of SERS will be greatly improved. Sandeep Surendra Panikar et al. used cellulose nanocrystals (CNCs) to form aerogels loaded with AuNPs, and then used aerogel collapse to achieve sensitive detection of organophosphorus pesticides in rice and tea extracts. However, its synthesis process is relatively complicated, the possibility of process and mass production is low, and the detection method is limited to analytes whose solvent is deionized water. However, most harmful substances such as antibiotics and pesticides are difficult to dissolve in water, which greatly affects the SERS detection of actual samples. Summary of the invention
[0005] The purpose of the present invention is to provide a three-phase sample contamination inspection method based on aerogel three-dimensional SERS, which utilizes the high hydrophilicity, porosity, high specific surface area and ultra-low density of starch aerogel to perform rapid and accurate SERS quantitative analysis of pollutants in the gas phase, liquid phase and solid phase.
[0006] To achieve the above object, the present invention provides a three-phase sample contamination inspection method based on aerogel three-dimensional SERS, comprising the following steps:
[0007] Step 1: synthesizing reducing agent dialdehyde starch using cassava starch as raw material;
[0008] Step 2: Prepare silver-loaded highly hydrophilic starch aerogel as SERS substrate;
[0009] Step 3: Select SERS probe molecules for sample detection to obtain SERS spectra;
[0010] Step 4: Perform gas-liquid-solid three-phase detection.
[0011] Optionally, the execution process of step 1 is specifically as follows: using cassava starch as a raw material and sodium periodate as an oxidant to selectively oxidize the 2,3-o-dihydroxyl group of cassava starch into an aldehyde group; taking 0.2g of cassava starch and 0.2g of sodium periodate in a 100mL beaker, adding 20mL of deionized water, stirring thoroughly, adding sulfuric acid dropwise to keep the pH of the system at 3.0, and reacting at room temperature in the dark for 5 hours; after the reaction is completed, separating the generated white solid by centrifugation; then suspending the solid in deionized water and centrifuging again, repeating this step 3 to 5 times until there is no more iodate or sulfuric acid in the supernatant liquid detected by starch-potassium iodide test paper, and the solution is neutral, freeze-drying the product for 12 hours, taking it out and grinding it to obtain the product dialdehyde starch.
[0012] Optionally, during the execution of step 2, 0.2g of cassava starch and 0.2g of sodium periodate are reacted in a 100mL beaker to obtain dialdehyde starch with a dialdehyde mole fraction of 80.76%. A certain mass of cassava starch and 0.1g of dialdehyde starch are mixed, 10mL of deionized water is added and heated to gelatinization, a certain volume of Tollens reagent is added dropwise, and after reacting for 5 minutes, the formed sol is dropped into a 96-well plate using a pipette and fixed and aged for 12 hours at 2-4°C, and finally freeze-dried to obtain the SERS substrate-loaded silver high-hydrophilic starch aerogel.
[0013] Optionally, during the execution of step 3, organic dyes rhodamine 6G and crystal violet are selected as SERS probe molecules, and 50 μL of rhodamine 6G and crystal violet of different concentrations are dropped on the surface of the silver-loaded high-hydrophilic starch aerogel to collapse it and then dried at 80°C for 10 minutes; a laser confocal micro-Raman spectrometer is used to perform sample detection on the best SERS substrate, and a laser wavelength of 532 nm is selected, with an exposure time of 1 s and a power of 10% to obtain all SERS spectra.
[0014] Optionally, in step 4, the detection of the gas phase is to utilize the porosity of the highly hydrophilic starch aerogel loaded with silver to absorb the harmful gas p-aminothiophenol; the detection of the solid phase is in situ detection on the apple surface; and the detection of the liquid phase adopts the standard addition method to determine the recovery rate of the apple juice sample.
[0015] The present invention provides a three-phase sample contamination inspection method based on aerogel three-dimensional SERS, using cassava starch (CS) as a supporting structure and dialdehyde starch (CDS) as a reducing agent, preparing silver-loaded starch aerogel (ACA) by freeze drying, characterizing the change of the distance between AgNPs on the aerogel surface before and after the collapse of ACA by SEM, TEM, etc., proving the increase of SERS hot spots, characterizing the group change and element composition of ACA in the synthesis process by FTIR, XPS, etc., and studying the adsorption isotherm and kinetics of ACA by BET. In practical applications, the present invention successfully utilizes the high specific surface area and high adsorption of ACA to successfully detect gaseous 4-ATP, and utilizes the collapse property to realize the trace detection of solid and liquid TBZ on the surface and in apples. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 It is a schematic flow chart of the steps of a three-phase sample contamination inspection method based on aerogel three-dimensional SERS of the present invention.
[0018] Figure 2 These are the corresponding spectra of ACA, cassava starch (CS), dialdehyde starch (CDS), and starch aerogel (CA) according to the embodiments of the present invention.
[0019] Figure 2 a is a UV-Vis comparison chart.
[0020] Figure 2 b is the FTIR comparison chart.
[0021] Figure 2 c is the XPS spectrum of ACA.
[0022] Figure 2 d is the high-resolution spectrum.
[0023] Figure 3 Schematic diagram of SEM (ad) and TEM (ef) analysis of ACA according to an embodiment of the present invention.
[0024] Figure 4 Schematic diagram of the characteristics of ACA according to an embodiment of the present invention.
[0025] Figure 4 a is a schematic diagram of particle size distribution.
[0026] Figure 4 b is the XRD pattern.
[0027] Figure 4 c is a schematic diagram of the N2 adsorption isotherm and BJH pore size distribution curve.
[0028] Figure 4 d is a schematic diagram of the height change of ACA before and after collapse.
[0029] Figure 5 1 is a Raman spectrum and standard curve diagram of R6G and CV at different concentrations on substrates ACA (ad), ATA (ef) and APA (gh) in the examples of the present invention.
[0030] Figure 6 Schematic diagram of the SERS performance of ACA in the embodiment of the present invention, repeatability (ab), reproducibility (cd) and stability (e).
[0031] Figure 7 It is the SERS and standard curve of the gas-solid-liquid three-phase detection of ACA in the embodiment of the present invention, and a schematic diagram of the effects of different substances in apple on TBZ. DETAILED DESCRIPTION
[0032] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0033] Explanation of English abbreviations used in this article:
[0034] SERS: surface enhanced Raman spectroscopy;
[0035] CS: tapioca starch;
[0036] CDS: dialdehyde starch;
[0037] ACA: silver-loaded starch aerogel;
[0038] CA: starch aerogel;
[0039] 4-ATP: p-aminothiophenol.
[0040] EM: Electromagnetic Enhancement
[0041] CM: Chemically Enhanced
[0042] TBZ: Thiabendazole
[0043] SEM: Scanning Electron Microscope
[0044] TEM: Transmission Electron Microscope
[0045] FTIR: Fourier Transform Infrared Absorption Spectrometer
[0046] XPS: X-ray Photoelectron Spectroscopy
[0047] BET: Specific surface area test method
[0048] XRD: X-ray diffraction
[0049] CV: Crystal Violet
[0050] R6G: Rhodamine 6G
[0051] ATA: Potato Starch Aerogels Loaded with Silver
[0052] APA: Silver-loaded pea starch aerogels
[0053] UV-Vis: Ultraviolet Visible Spectroscopy
[0054] See also Figure 1 The present invention provides a three-phase sample contamination inspection method based on aerogel three-dimensional SERS, comprising the following steps:
[0055] S1: Synthesis of reducing agent dialdehyde starch using cassava starch as raw material;
[0056] S2: Preparation of silver-loaded highly hydrophilic starch aerogel as SERS substrate;
[0057] S3: Select SERS probe molecules to detect samples and obtain SERS spectra;
[0058] S4: Perform gas-liquid-solid three-phase detection.
[0059] The following is further described in conjunction with specific embodiments and execution steps:
[0060] (1) Synthesis of reducing agent CDS
[0061] Take 0.2g CS and 0.2g sodium periodate and place them in a 100mL beaker, add 20mL deionized water, stir thoroughly, add sulfuric acid (1M) dropwise to keep the pH of the system at 3.0, and react at room temperature in the dark for 5h. After the reaction is completed, separate the white solid by centrifugation. Then suspend the solid in deionized water and centrifuge again, repeat this step 3 to 5 times until there is no iodate or sulfuric acid in the supernatant by starch-potassium iodide test paper, and the solution is neutral. Freeze-dry the product for 12h, take it out and grind it to obtain the product CDS.
[0062] (2) Synthesis of substrate ACA
[0063] 0.2g CS and 0.2g sodium periodate were reacted in a 100mL beaker to obtain CDS with a dialdehyde molar fraction of 80.76%. A certain mass of CS and 0.1g of CDS were mixed, 10mL of deionized water was added and heated to gelatinization, a certain volume of Tollens reagent was added, and after reacting for 5 minutes, the formed sol was dropped into a 96-well plate using a pipette and fixed and revived at 2-4℃ for 12 hours, and finally freeze-dried to obtain the SERS substrate ACA.
[0064] The synthesis of ACA utilizes the unique gelatinization and retrogradation properties of starch. Starch is mainly composed of amylose and amylopectin. During the gelatinization process, starch granules absorb water and swell. After the starch molecular chains are stretched, they are entangled with each other in the form of double helices to form a gel network. After being placed at low temperature, the hydrogen bonds between adjacent molecules gradually form dense starch molecular micro-bundles, which are hydrogels. After the hydrogel is freeze-dried, an aerogel with a three-dimensional network structure with uniform pores inside is formed. Dialdehyde starch (CDS) and cassava starch (CS) are mixed to make aerogels, in which CS is used as the supporting structure of the aerogel and CDS is used as a reducing agent to reduce AgNPs. The experimental process is to first mix CS and CDS in different ratios (6:1, 5:1, 4:1, 3:1, 2:1) and gelatinize them, then add 1 ml of Tollens reagent, then drop the sol obtained by the reaction in a 96-well plate for setting and retrogradation at 2-4℃ for 12 hours, and finally freeze-dry for 24 hours to obtain ACA.
[0065] Specifically, Figure 2 a is the UV-Vis spectrum of the prepared silver-loaded starch aerogel (ACA). ACA generates surface plasma resonance under the action of light, which in turn enhances the local electromagnetic field intensity near the particle surface, and the ultraviolet absorption peak appears at 420nm. CA, CDS, and CS have no obvious absorption peaks in the range of 300-800nm. In the FTIR image ( Figure 2 b) The aldehyde group in CDS is at 1735 cm -1 The absorption peak generated at did not appear in ACA, which indicates that the aldehyde group may participate in the chemical reaction. There is no significant difference between CS and cassava starch aerogel (CA), indicating that the chemical structure of CS has not changed much before and after gelatinization. Figure 2 cd is the full spectrum and fine spectrum of ACA. The full spectrum is composed of the peaks of Ag, C, O, N and other elements, and the fine spectrum is the characteristic peaks of Ag 3d5 / 2 and Ag 3d3 / 2 at 367.4eV and 373.4eV. Combined with XPS, FTIR and UV-Vis analysis, it was confirmed that Ag NPs were successfully generated and loaded on the surface of starch aerogel.
[0066] The surface morphology of the prepared ACA before and after collapse is as follows Figure 3 As shown in ad, before collapse, ACA showed a well-defined three-dimensional porous structure ( Figure 3 a), after collapse, the three-dimensional porous structure of the aerogel disappears and a dense plane is formed ( Figure 3 b). The Ag NPs loaded on the surface of the aerogel gradually approach each other as the aerogel collapses, and the generated SERS hotspots also gradually increase ( Figure 3 cd).
[0067] In addition, TEM analysis was performed ( Figure 3 e), first of all, it can be clearly seen in the figure that the reaction forms typical silver nanospheres. Then TEM is used to determine the particle size distribution of the nanoparticles loaded on the aerogel. The obtained TEM is analyzed using NanoMeasurer 1.2 software, and the average size distribution of about 100 particles is calculated and plotted into a histogram, as shown in Figure 4 The particle size of the synthesized Ag NPs shown in (a) is about 16.1 nm. Figure 4 b), cassava starch has four obvious diffraction peaks at 15.1°, 17.9°, 18.1°, and 23.1°, which belong to the typical A-type crystal structure. The diffraction pattern of CA has no diffraction peaks, showing the characteristics of amorphous structure, and the relative crystallinity is significantly reduced. This is because the particle structure of cassava starch is destroyed and the crystal structure disappears due to high temperature. 38.2°, 44.4°, 64.6°, and 77.6° correspond to planes (111), (200), (220), and (311), respectively. This diffraction peak is consistent with the data of PDF#87-0720. This once again verifies the growth of AgNPs on the surface of aerogel.
[0068] Finally, the BET specific surface area and porous structure of CA and ACA were characterized by N2 adsorption-desorption analysis. Figure 4 c shows the N2 adsorption isotherms and BJH pore size distribution curves of CA and ACA (inset). In the low-pressure stage, N2 molecules are adsorbed on the inner surface of ACA in monolayer to multilayer, indicating that there are a certain amount of micropores; in the high-pressure stage, the desorption isotherm and the adsorption isotherm do not overlap, indicating that the adsorption behavior is caused by the macropores in the aerogel. According to the six types of adsorption-desorption isotherms classified by the International Union of Pure and Applied Chemistry (IUPAC), the N2 adsorption-desorption isotherm of starch aerogel belongs to the type IV isotherm and forms a hysteresis loop, indicating that there is a grading phenomenon in the pore size in the aerogel. The specific surface areas of CA and ACA are 4.387 m 2 / g and 1.400m 2 / g, and the decrease in specific surface area may be due to the adsorption of Ag NPs on the aerogel.
[0069] In order to test the water sensitivity of ACA, about 50 μL of analyte solution (aqueous solution) was dropped on the surface of ACA and then dried at 80°C for 5 min. Figure 4 In d, the height of ACA before collapse is about 0.33 cm, and the thickness of ACA after collapse is about 0.13 mm, indicating that the collapse effect of ACA is good.
[0070] (3) Sample preparation and SERS measurement
[0071] In order to evaluate the sensitivity, stability, repeatability and reproducibility of the SERS substrate ACA, this patent selected organic dyes Rhodamine 6G (R6G) and crystal violet (CV) as SERS probe molecules. 50 μL of R6G and CV of different concentrations were dropped on the surface of the aerogel to collapse it and then dried at 80 ° C for 10 minutes. The best SERS substrate was sampled using a laser confocal micro-Raman spectrometer, and the laser wavelength was selected as 532nm laser, 1s exposure time and 10% power to obtain all SERS spectra.
[0072] The SERS performance of ACA mainly includes the ability of quantitative detection, stability, repeatability and reproducibility. First, the quantitative detection of ACA was studied. Figure 5 a, c show the effects of ACA and different concentrations of R6G (10 -5 -10 -10 M) and CV(10 -5 -10- 10 M) SERS spectra after hybrid collapse. R6G and CV at 614 cm -1 and 1622cm -1 The Raman intensity at 614cm -1 and 1622cm -1 A linear relationship between the SERS intensity and the concentrations of R6G and CV was established ( Figure 5 b, d, the results show that there is a good linear relationship between the two (y = 0.442x + 7.18 and y = 0.433x + 7.26) and the correlation coefficient (R 2 ) were 0.996 and 0.997, respectively. Therefore, quantitative analysis of R6G and CV with high sensitivity and wide concentration range can be achieved.
[0073] Secondly, the quantitative detection capabilities of ATA and APA were also examined. The experimental results showed that ATA was more sensitive than APA in detecting R6G. Figure 5eh). This may be due to the large number of holes in the substrate after APA collapse. The linear relationships of ATA and APA for R6G are y=0.507x+7.54 and y=0.526x+7.50 respectively, and the correlation coefficient (R 2 ) are 0.991 and 0.980 respectively.
[0074] Finally, the stability, repeatability and reproducibility of ACA were studied. The differences in SERS intensity at different sampling locations on the same substrate were compared, such as Figure 6 a, randomly select 20 points on the substrate and measure 10 -6 The SERS intensity of MR6G is relatively uniform. -1 The relative standard deviations (RSD) of the intensities at Figure 6 b) and SERS imaging was performed at the characteristic peak of 614 cm-1 ( Figure 6 c). Both of them show that the substrate has good repeatability. Five different batches of ACA were selected to measure 10 -6 Spectrum of MR6G, RSD( Figure 6 d) were 3.5%, respectively, proving that the reproducibility of the substrate is relatively good. R6G (10-6M) was used to compare the same batch of ACA at different times. Figure 6 e. The SERS performance of the material was measured every 30 days. The characteristic peak of R6G at 614 cm -1 The intensity did not change significantly, indicating that the stability of the substrate is also relatively good.
[0075] (4) Gas-liquid-solid three-phase detection
[0076] Gas detection is to use the porous nature of ACA to absorb harmful gas p-aminothiophenol (4-ATP). This paper adopts the Long-kunYang method to generate gas-phase 4-ATP molecules. A certain volume of 4-ATP alcohol solution is added to a beaker and heated at 80°C. ACA is adhered to a glass slide with double-sided tape and then inverted on the beaker and sealed with plastic wrap to achieve the adsorption equilibrium of gas-phase 4-ATP in the beaker. 50μL of deionized water is dropped on the surface of ACA to collapse the aerogel and dry it for 10 minutes before SERS detection.
[0077] So far, gas-phase SERS detection remains extremely challenging due to the low affinity of airborne species to metal surfaces. ACA, with its large surface area before collapse and high density of "hot spots" after collapse, would be an ideal solution for gas-phase SERS detection. ACA reached gas-phase 4-ATP adsorption equilibrium in a closed beaker while dripping and collapsing, after which further SERS measurements were performed. 30 spectra were measured at different concentrations (200 mg / L, 100 mg / L, 50 mg / L, 10 mg / L, 5 mg / L, 1 mg / L). Figure 7 ab show the representative SERS spectra of 4-ATP at different concentrations from 200 mg / L to 1 mg / L and ACA at 1075 cm in 50 mg / L to 1 mg / L. -1 There is a good linear relationship (y = 5438.2x + 160.6) and the correlation coefficient (R 2 ) is 0.996. This reliable detection of gas demonstrates the unique advantage of ACA over traditional precious metal aggregates. The minimum detection limit of TBZ was calculated using LOD=3Sb / M, where Sb is the standard deviation of the SERS intensity of the blank sample at the characteristic peak; M is the slope of the drawn calibration curve. The calculated LOD is 0.64 mg / L. ACA exhibits extraordinary SERS stability in the air. Unlike traditional SERS substrates, this stable substrate in the form of aerogel is easy to store and use, facilitating on-site SERS "nose" applications, such as fast and reliable gas detection chemical analysis, food safety inspections, and counter-terrorism.
[0078] The solid phase detection is an in-situ detection on the apple surface. First, a standard curve of TBZ with different concentrations (50 mg / L, 10 mg / L, 5 mg / L, 1 mg / L, 0.5 mg / L, 0.25 mg / L, 0.1 mg / L) is established in a methanol solution. Secondly, 1 mL of TBZ with different concentrations (10 mg / L, 5 mg / L, 1 mg / L) is sprayed on the surface of the apple with a syringe overnight to wait for the methanol to evaporate. Finally, 50 μL of methanol is dropped on the surface of the ACA to wipe the surface of the positive apple, and dried at 80 ° C for 1 min. After the organic solvent methanol evaporates, 50 μL of deionized water is dropped to collapse it and then dried for 10 min before SERS measurement.
[0079] In practical applications, wipe sampling is considered to be the most widely adopted sampling method and portable analytical method for surface contamination. In order to evaluate the practical application of SERS of ACA, thiabendazole was used as the test probe molecule. TBZ is a systemic benzimidazole fungicide and parasite cleaner that has been widely used in agricultural products to prevent rot and wilt caused by fungal infection in vegetables and fruits during transportation and long-term storage. In general, TBZ is less toxic than other pesticides, but high doses may still cause thyroid hormone imbalance and liver damage. The U.S. Environmental Protection Agency (EPA) lists it as a carcinogen. TBZ can be used for fruit preservation in a strictly controlled manner, with a maximum usage limit of 20 mg / L. Therefore, it is particularly urgent to develop sensitive and rapid site detection methods.
[0080] The detailed ACA swab test is as follows. The substrate ACA is used to quantitatively detect different concentrations (50 mg / L, 10 mg / L, 5 mg / L, 1 mg / L, 0.5 mg / L, 0.25 mg / L, 0.1 mg / L) of TBZ in methanol solution. The intensity of the SERS spectrum decreases as the TBZ concentration decreases from 50 ppm to 0 ppm ( Figure 7 c), which indicates that the TBZ concentration is positively correlated with the SERS spectrum intensity. Figure 7 d is at 781cm -1 The linear relationship between the SERS intensity of the characteristic peak at and the logarithm of TBZ concentration is y = 2524.3x + 1231.6, and the correlation coefficient R 2 =0.979 and LOD is 0.053 mg / L. Therefore, the SERS spectrum intensity can be used for the quantitative analysis of TBZ in methanol solution.
[0081] In order to verify the accuracy and reliability of the SERS substrate ACA, 10mg / L, 5mg / L, and 1mg / L TBZ were dropped on the surface of apples overnight, and then wiped with ACA filled with methanol. The spike recovery rate was studied. The recovery rate of TBZ was 95.0-99.4%, which has a good food safety detection effect. In addition, SERS measurements were performed on the remaining concentrations used for fitting (50mg / L, 0.5mg / L, 0.25mg / L, 0.1mg / L). Figure 7 e is at 781cm -1 The linear relationship between the SERS intensity of the TBZ characteristic peak on the apple surface and the logarithm of the TBZ concentration is y = 2406.7x + 2521.6, and the correlation coefficient is R 2 =0.980 and LOD is 0.067 mg / L.
[0082] Liquid phase detection is more traditional and consistent with solid phase detection and the method of establishing a standard curve. The recovery rate of apple juice samples was determined by the standard addition method. 3 mL of TBZ with different concentrations (50 mg / L, 10 mg / L, 5 mg / L, 1 mg / L, 0.5 mg / L, 0.25 mg / L, 0.1 mg / L) was mixed with 1 ml of apple juice, and then 1 mL of 1% acetonitrile was added and stirred evenly. Then 0.4 g MgSO4 and 0.17 g CH3COONa were added and centrifuged at 8000 rpm for 5 min. 50 μL of the supernatant was dropped on the surface of ACA and dried at 80 ° C for 5 min. After the organic solvent acetonitrile evaporated, 50 μL of deionized water was dropped to make it collapse and dried for 10 min. Finally, SERS measurement was performed.
[0083] The lowest concentration of TBZ in the actual sample was investigated. SERS test was performed on TBZ at 0.1-50 mg / L. When the TBZ concentration was lower than 0.1 mg / L, the peak at 781 cm -1 and 1009cm -1 The characteristic peaks are difficult to identify. Figure 7 fg recorded the SERS spectra of TBZ at different concentrations (50 mg / L, 10 mg / L, 5 mg / L, 1 mg / L, 0.5 mg / L, 0.25 mg / L, 0.1 mg / L) in apple juice samples. The sample without TBZ was used as the control sample. After adding TBZ, as the concentration of TBZ decreased, the SERS spectra at 781 cm -1 The SERS peak intensity of the characteristic peak will also decrease. In apple juice, 781cm -1 The standard curve at is y = 2538.7x + 2522.4, R 2 The calculated result of LOD is 0.063 mg / L, so this method can stably judge the positive simulation samples.
[0084] In addition, the anti-interference performance and selectivity performance of the method of the present invention are studied in the examples. Inorganic and organic substances that may coexist in apple juice are selected, including Ca + , K + Mg + 、Na + , Cl - , vitamin C thiram, acetamiprid. Figure 7 h shows that when these substances are used as interfering substances, TBZ is at 781 cm -1 The SERS signal change rate at the position is less than 4.8%, indicating that the substances that may coexist in the actual sample have little interference with thiabendazole and ACA has good selectivity for thiabendazole, proving that this method can be used to detect residual thiabendazole in apple juice.
[0085] In summary, the present invention successfully detected gaseous 4-ATP by utilizing the high specific surface area and high adsorption of ACA, and realized the trace detection of solid and liquid TBZ on the surface and in apples by utilizing the collapse property. This method has opened up a broad space for the application of SERS in food safety and environmental safety;
[0086] The gas-liquid-solid three-phase substances were analyzed using p-aminothiophenol (4-ATP) and thiabendazole, verifying the practical application of ACA as a gas-liquid-solid three-phase detection material. The synthesized multifunctional integrated material ACA has great potential in the application of SERS. Starch-based SERS substrates have the advantages of low pollution, high cost-effectiveness of raw materials, simple preparation methods, good biocompatibility, etc., which creates unlimited possibilities for the application of new SERS substrates in various fields.
[0087] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A three-phase sample contamination inspection method based on aerogel three-dimensional SERS, characterized in that: The following steps are involved: Step 1: synthesizing reducing agent dialdehyde starch using cassava starch as raw material; Step 2: Prepare silver-loaded highly hydrophilic starch aerogel as SERS substrate; Step 3: Select SERS probe molecules for sample detection to obtain SERS spectra; Step 4: Perform gas-liquid-solid three-phase detection.
2. The three-phase sample contamination inspection method based on aerogel three-dimensional SERS according to claim 1, characterized in that: The execution process of step 1 is specifically as follows: using cassava starch as a raw material and sodium periodate as an oxidant to selectively oxidize the 2,3-o-dihydroxyl group of cassava starch into an aldehyde group; taking 0.2g of cassava starch and 0.2g of sodium periodate in a 100mL beaker, adding 20mL of deionized water, stirring thoroughly, adding sulfuric acid dropwise to keep the pH of the system at 3.0, and reacting at room temperature in the dark for 5 hours; after the reaction is completed, separating the generated white solid by centrifugation; then suspending the solid in deionized water and centrifuging again, repeating this step 3 to 5 times until no iodate or sulfuric acid is found in the supernatant by starch-potassium iodide test paper, and the solution is neutral, freeze-drying the product for 12 hours, taking it out and grinding it to obtain the product dialdehyde starch.
3. The three-phase sample contamination inspection method based on aerogel three-dimensional SERS according to claim 2, characterized in that: During the execution of step 2, 0.2 g of cassava starch and 0.2 g of sodium periodate were reacted in a 100 mL beaker to obtain dialdehyde starch with a dialdehyde molar fraction of 80.76%; a certain mass of cassava starch and 0.1 g of dialdehyde starch were mixed, 10 mL of deionized water was added and heated to gelatinization, a certain volume of Tollens reagent was added dropwise, and after reacting for 5 minutes, the formed sol was dropped into a 96-well plate using a pipette and fixed and regenerated at 2-4°C for 12 hours, and finally freeze-dried to obtain the SERS substrate-loaded silver high-hydrophilic starch aerogel.
4. The three-phase sample contamination inspection method based on aerogel three-dimensional SERS according to claim 3, characterized in that: During the execution of step 3, organic dyes rhodamine 6G and crystal violet were selected as SERS probe molecules, and 50 μL of rhodamine 6G and crystal violet of different concentrations were dropped on the surface of silver-loaded high-hydrophilic starch aerogel to make it collapse and then dried at 80°C for 10 minutes; a laser confocal micro-Raman spectrometer was used to perform sample detection on the best SERS substrate, with a laser wavelength of 532 nm, an exposure time of 1 s and a power of 10%, to obtain all SERS spectra.
5. The three-phase sample contamination inspection method based on aerogel three-dimensional SERS according to claim 4, characterized in that: In step 4, the detection of the gas phase is to use the porosity of the highly hydrophilic starch aerogel loaded with silver to absorb the harmful gas p-aminothiophenol; the detection of the solid phase is in situ detection on the apple surface; and the detection of the liquid phase adopts the standard addition method to determine the recovery rate of the apple juice sample.
Citation Information
Patent Citations
Preparation and application of nano-silver-carrying PNIPAM / PVA composite thermosensitive gel
CN106423291A
Acoustic suspension droplet concentration method and method for realizing multi-component and multi-phase trace detection
CN115452544A
Reduced graphene oxide-silver aerogel SERS (Surface Enhanced Raman Scattering) substrate, preparation method and application
CN116087169A
Method for detecting organic dye in water based on self-assembled temperature-sensitive SERS (Surface Enhanced Raman Scattering) substrate
CN117388232A
Dynamic controllable hydrogel SERS (Surface Enhanced Raman Scattering) substrate as well as application and preparation method thereof
CN117849336A